2005
DOI: 10.1186/1477-5751-4-9
|View full text |Cite
|
Sign up to set email alerts
|

Beta-defensin genomic copy number is not a modifier locus for cystic fibrosis

Abstract: Human beta-defensin 2 (DEFB4, also known as DEFB2 or hBD-2) is a salt-sensitive antimicrobial protein that is expressed in lung epithelia. Previous work has shown that it is encoded in a cluster of beta-defensin genes at 8p23.1, which varies in copy number between 2 and 12 in different individuals. We determined the copy number of this locus in 355 patients with cystic fibrosis (CF), and tested for correlation between beta-defensin cluster genomic copy number and lung disease associated with CF. No significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 28 publications
(27 reference statements)
3
23
0
Order By: Relevance
“…Consistent with previous data (18)(19)(20)(21), copy number among the parents of these 26 families varied between 2 and 7, with a modal copy number of 4 and a mean of 4.58. We observed that at least 24 offspring inherited recombinant haplotypes in which parental copies of the ␤-defensin repeat had been reassorted.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…Consistent with previous data (18)(19)(20)(21), copy number among the parents of these 26 families varied between 2 and 7, with a modal copy number of 4 and a mean of 4.58. We observed that at least 24 offspring inherited recombinant haplotypes in which parental copies of the ␤-defensin repeat had been reassorted.…”
Section: Resultssupporting
confidence: 76%
“…S1), such that completely null (zero-copy) haplotypes could be created by simple allelic recombination between such chromosomes. By contrast, in typing Ͼ1,500 unrelated individuals for ␤-defensin copy number (18)(19)(20)24), we have observed only a single example of an individual with 1 copy, suggesting that zero-copy haplotypes are infrequent and may be very rare. However, a zero-copy haplotype is most likely to be found in combination with a 2-copy haplotype and thus will escape unambiguous detection by diploid copy number measurement alone; we do not yet have sufficiently precise data on frequencies of haplotypes with different copy numbers at each site to establish whether the observed frequency of 1-copy individuals represents a significant departure from the predictions of a neutral model.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…Most HBD genes are found in a cluster at 8p23.1 , which is polymorphic in copy number (Hollox et al 2005). Individuals have 2-12 copies of this repeat per diploid genome.…”
Section: Defensinsmentioning
confidence: 99%